Medical microbiology a guide to microbial infections : pathogenesis, immunity, laboratory diagnosis, and control - Barer, Michael R; Irving, Will; Swann, Andrew; Perera, Nelun (Elsevier, 2019)
Medical microbiology concerns the nature, distribution and activities of microbes and their impact on health and wellbeing. In spite of the introduction of many antimicrobial agents and immunisations, we continue to face major challenges in combatting infection, not least the gathering crisis in antimicrobial resistance.